The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c6sm02464e
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular nanoparticle dynamics affected by cytoskeletal integrity

Abstract: The cell interior is a crowded chemical space, which limits the diffusion of molecules and organelles within the cytoplasm, affecting the rates of chemical reactions. We provide insight into the relationship between non-specific intracellular diffusion and cytoskeletal integrity. Quantum dots entered the cell through microinjection and their spatial coordinates were captured by tracking their fluorescence signature as they diffused within the cell cytoplasm. Particle tracking revealed significant enhancement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 53 publications
(63 reference statements)
3
49
0
Order By: Relevance
“…Thus, it is possible that the increased stiffness resulting from noco treatment in fibrosarcoma cells is the cause of the decrease of mitochondrial movement that occurred. This same result is also reflected in intracellular particle dynamics measurements where the particles decrease in motility within noco-treated fibrosarcoma cells but not noco-treated fibroblasts ( Grady et al, 2017 ). Disruption of microtubules in cancer cells affects both cell elasticity and mitochondrial locomotion ( Kandel et al, 2015 ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, it is possible that the increased stiffness resulting from noco treatment in fibrosarcoma cells is the cause of the decrease of mitochondrial movement that occurred. This same result is also reflected in intracellular particle dynamics measurements where the particles decrease in motility within noco-treated fibrosarcoma cells but not noco-treated fibroblasts ( Grady et al, 2017 ). Disruption of microtubules in cancer cells affects both cell elasticity and mitochondrial locomotion ( Kandel et al, 2015 ).…”
Section: Discussionmentioning
confidence: 55%
“…Altering the actin network in the fibroblasts cell line with CytD treatment increased the diffusion coefficient to 1.3E-3 μm 2 /s, a value similar to that obtained with the fibrosarcoma cells. Based on our work with nanoparticle diffusion we believe the apparent differences in the diffusion of mitochondria within fibrosarcoma cells is due to the more open cytoskeletal network ( Grady et al, 2017 ). This result is further emphasized by the increased mitochondria diffusion in fibroblast cells where the application of CytD has opened the cytoskeletal network.…”
Section: Resultsmentioning
confidence: 99%
“…From a structural point of view, a major barrier to diffusion is the cytoskeleton. Using different methods, mesh sizes in the range of 30–100 nm were found, although even smaller particles of 10 nm were restricted in their movement by the actin cytoskeleton . A second barrier to diffusion, notably in the perinuclear region, is constituted by the endoplasmatic reticulum (ER) and the Golgi apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…The cytoplasm is a mesh-like cytoskeletal network and macromolecular crowding in which only particles with a diameter less than 50 nm can diffuse freely, which inevitably increase the steric hindrance and random collision for the diffusion of lipoplexes or dissociative DNA ( Figure 3 ). 20 , 21 , 129 An earlier study by Lukacs et al. 130 found that only small DNA fragments (<250 bp) diffused rapidly to the nucleus by Brownian motion after microinjection into the cytoplasm, and the movement of the larger counterpart (>2,000 bp) was almost retarded.…”
Section: Main Textmentioning
confidence: 99%
“… 19 Furthermore, the reticular cytoskeletal network and the macromolecular crowding in the cytoplasm are not conducive to the transport of lipoplexes or DNA to the nucleus. 20 , 21 Therefore, even though CLs have been considered to be the most promising nanocarriers for cancer gene therapy, gene delivery to target sites is bumpy, because CLs, as invaders, face a series of events such as opsonization, rapid clearance by the RES, poor tumor penetration, cellular uptake, and lysosomal degradation, resulting in therapeutic failure in the body.…”
Section: Main Textmentioning
confidence: 99%